An intervention study for impact assessment of health education by empowered community health workers in improving treatment and diet adherence in hypertension - Mifetika Lukitasari; Dwi Adi Nugroho; Mohammad Saifur Rohman; Hanna Mardhotillah; Dennis Eristya Natasya; Fitriyawati Fitriyawat; Niko Dima Kristianingrum; Ahmad Hasyim Wibisono (Wolters Kluwer Medknow Publications, 2021)
Context: Medication and low salt diet adherence play as an essential factor in blood pressure target achievement. Community health worker empowerment was reported to be a highly effective social intervention to medication and low salt diet adherence. Aims: This study aimed to investigate the effect of structured health education regarding hypertension on community health workers on medication and low salt diet adherence among hypertensive patients in Malang. Subjects and Methods: A quasi-experimental study was conducted in health workers and their hypertensive patients who join in the Integrated Health Service Post for the Elderly (IHSP-Elderly) program in Malang. Medication adherence was measured by the medication adherence questionnaire and low salt diet adherence was measured by dietary salt restriction questionnaire. The data were analyzed by Chi-square analysis for categorical data and independent t-test for numerical data. Results: This study showed that hypertensive patients in the intervention group had better knowledge regarding hypertension compared to those of the control group (P < 0.05). The patients' satisfaction in intervention group improved significantly after health education (P < 0.01). The proportion of patients with good medication adherence improved significantly (P < 0.01) from 20% to 70% after health education in intervention group. Moreover, the proportion of patients with good low salt diet compliance improved significantly (P < 0.01) from 39% to 85%. Conversely, the proportion of good medication and low salt diet adherence in control group relatively similar between pre- and post-test. Conclusions: This study showed that health education on community health workers improved hypertensive patients' medication and low salt diet adherence.